Knowledge, attitude, and behaviour of physical education and sports students’ about dietary supplements: Dietary supplement use of sports students - Tevfikoglu Pehlivan, Leyla; Ateş Özcan, Burcu; Erem, Sinem; Ercan, Aydan; Akkaya, İzel and Başarır, Aylin (Progress in Nutrition, 2020)
Study Objectives: This study was carried out to determine the knowledge, attitude, and behavior of sports students’ about dietary supplements. Method: This study was carried out voluntarily by applying face-to-face questionnaires with 145 students aged 18-25, 37.9% female, and 62.1% male, studying at Trakya University School of Physical Education and Sports. The questionnaire includes demographic information of the participants, information and use of dietary supplements, and anthropometric measurements. Results: 45.5% of the students used dietary support, and the rate of dietary support usage of males (30.3%) was higher than dietary support usage of females (15.2%) (p>0.05). It was found that 11.7% of the students received information from doctors / dieticians, 13.8% from trainers, and 18.6% from other sources (internet, television, friends) (p<0.05). It was determined that the students mostly heard about branched chain amino acids, amino acids, and coenzyme Q10 dietary supplements and they tried and quit products such as protein powder, multivitamin, and n-3 fatty acids. Participants stated that they mostly used caffeine, protein powder, and n-3 fatty acid supplements. The majority of the students stated that dietary supplements provide energy, do not benefit in irregular use, affect performance when used with physical activity, excessive protein supplements or any supplements to increase muscle mass will be beneficial, even if they are fed adequate and balanced nutrition, they should take supplements or in excess doses. They also stated that they do not have sufficient information about the label information of dietary supplements and their harmful effects in long-term use. Conclusion: Sports students got information about dietary supplements from the internet and their friends. There is a need for more widespread information about the correct use of individuals who do sports by obtaining information from correct sources, specific to the individual and under appropriate conditions.